Testing common knowledge: are Northern Europeans and millennials more concerned about the environment? - Gómez-Román, C.; Lima, M. L.; Seoane, G.; Alzate, M.; Dono, M.; Sabucedo, J.-M. (Sustainability, 2021)
This study explores whether there are differences in several environmental dimensions, when the European Region and Generation cohort are considered. In doing so, this study compares millennials in North and South Europe with members of Generation X in three environmental dimensions: attitudes, personal norms, and behavior. Using data from the European Social Survey (n = 6.216), the researchers tested the hypothesis that Northern Europeans and millennials have more pro-environmental standing than southerners and Generation Xers. The findings challenge the common belief that millennials are more committed to being environmentally conscious, showing that many millennials do not feel responsible for their climate footprint, nor do they behave in a way that shows more concern than previous generations to improve their environmental performance. Furthermore, contrary to expectations, Northern European participants are not the most committed, in all environmental dimensions, compared to Southern Europeans.